An Awkward Situation: Kosovo, the EU and EU Member States - Stępień, Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The paper is related to the legal effects of Kosovo’s international status on the relations between the EU and its member states. Kosovo is not recognized as a state by five of the EU member states. On the other hand, all the EU member states support theconclusion an association agreement between the EU and Kosovo (actually Stabilization and Association Agreements). According to the TFEU and EU practice, accession agreements are mixed ones. It means they are concluded together by the EU and its member states. However, in case of the Kosovo SAA, a different solution has been applied. The Kosovo SAA is a bilateral agreement between the EU and Kosovo. In addition, according to the provisions of this SAA, there is no implied recognition of Kosovo as a state by the EU. Such a solution may be, however, considered as exceeding the EU’s external competence. Thus, an awkward situation seems to need an awkward solution.
Keywords: państwowość Kosowa; nieuznawanie; Unia Europejska